Development of the methods of non-contact measuring of the slugs crystallizing process - D. E. Kritskij; V. T. Minchenja; A. D. Kritskij; A. N. Krutilin; A. I. Stanjuk (Литьë и металлургия)
There is presented the method of non-contact of the hardening processes of thin-walled cast iron wares.